STUDENTS’ PERCEPTION OF USING TED TALKS IN ENGLISH LISTENING SKILL - Erlan, Frerianta; Abduh, Amirullah; Tahir, Muh. (JTechLP: Journal of Technology in Language Pedagogy, 2024)
Listening is the beginning skill in learning a foreign language as people begin to learn a language from how it sounds before learning how it is written, and spoken. Listening skill is about receiving the message from sound, and voice. This research is conducted by the study of students’ perception of the use of TED talks videos in listening skills, to explore students' perception about using TED talks in English listening skills. This study applied qualitative method and the instrument using a questionnaire and an interview. There are 8 questionnaire questions and 11 interview questions were distributed to the participants. The participants who already filled out the questionnaire are 21 participants. The result from respondents through questionnaires and interviews indicates the students have a positive perception toward TED Talk videos to improve their listening skills therefore it could be seen that the listening skills material which was equipped with TED Talk videos as a media can improve listening skills in teaching learning English.